2019
DOI: 10.1097/ftd.0000000000000650
|View full text |Cite
|
Sign up to set email alerts
|

Preanalytical Stability of Piperacillin, Tazobactam, Meropenem, and Ceftazidime in Plasma and Whole Blood Using Liquid Chromatography–Tandem Mass Spectrometry

Abstract: Background: Therapeutic drug monitoring (TDM) is increasingly used to optimize the dosing of beta-lactam antibiotics in critically ill patients. However, beta-lactams are inherently unstable and degrade over time. Hence, patient samples need to be appropriately handled and stored before analysis to generate valid results for TDM. The appropriate handling and storage conditions are not established, with few and conflicting studies on the stability of beta-lactam antibiotics in clinical samples. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(66 citation statements)
references
References 30 publications
3
61
2
Order By: Relevance
“…Residual blood was stored at 4°C for up to 4 days (median, 3 days) before processing. Stability of piperacillin at this temperature for 3–4 days has been demonstrated previously 9 and reproduced by our own group (data not shown). Blood was centrifuged (2060 g , 10–20°C, 10 min), and the supernatant was stored at −80°C until free concentrations were measured.…”
Section: Methodssupporting
confidence: 83%
“…Residual blood was stored at 4°C for up to 4 days (median, 3 days) before processing. Stability of piperacillin at this temperature for 3–4 days has been demonstrated previously 9 and reproduced by our own group (data not shown). Blood was centrifuged (2060 g , 10–20°C, 10 min), and the supernatant was stored at −80°C until free concentrations were measured.…”
Section: Methodssupporting
confidence: 83%
“…These findings show stability for longer periods of time at 4°C than previous studies. Defining stability as less than 15% degradation, Mortensen and colleagues showed that piperacillin, tazobactam, meropenem, and ceftazidime were stable in whole blood and ethylenediaminetetraacetic acid (EDTA)‐anticoagulated plasma at 4°C for 3 days, 12 and Bugnon and colleagues observed cefepime stability in plasma for at least 12 hours at 4°C 14 . Another study showed decay of <15% of meropenem in plasma in 4 days at 6°C 26 .…”
Section: Discussionmentioning
confidence: 99%
“…For chromatographic assays, the Food and Drug Administration (FDA) defines stability as being ±15% of the original concentration 11 . Multiple studies have shown that various β‐lactam antibiotics, including piperacillin, cefepime, and meropenem, are stable at room temperature for only a few hours in whole blood or plasma, and some studies have shown β‐lactam stability for a few days at 4°C 9,10,12–14 . However, there is no agreement on the best practice for short‐term storage of beta‐lactam antibiotics to ensure stability.…”
mentioning
confidence: 99%
“…Studies have reported that β-lactams show substantial degradation in plasma depending on the storage temperature and storage time [4][5][6]. For meropenem, significant degradation has been shown beyond 6 h at 24 • C or 3 days at 4 • C [7]. Hence, plasma samples should be processed and frozen as soon as possible.…”
Section: Introductionmentioning
confidence: 99%